NI-19 Use of 11C-methionine PET for decision of discontinuation of adjuvant chemotherapy with temozolomide - Beppu, Takaaki; Sato, Yuichi; Sasaki, Toshiaki; Terasaki, Kazunori; Ogasawara, Kuniaki (Neuro-oncology advances, 2020)
Abstract Background: The aim was to clarify whether positron emission tomography with 11C-methyl-L-methionine (met-PET) is useful to decide on discontinuation of TMZ-adjuvant therapy in patients with residual diffuse astrocytic tumor. Methods: Subjects were 44 patients with residual tumor comprising 17 with IDH1-mutant diffuse astrocytoma (DA), 13 with IDH1-mutant anaplastic astrocytoma (AA), and 14 with IDH1-wild glioblastoma (GB). All patients received TMZ-adjuvant chemotherapy (median, 12 courses), and whether to discontinue or continue TMZ-adjuvant chemotherapy was decided on the basis of the tumor-to-normal ratio in standardized uptake value from met-PET (T/N); patients with T/N < 1.6 immediately discontinued TMZ, and patients with T/N > 1.6 were either to continued or discontinued TMZ. Progression-free survival (PFS) was compared between patients with T/N > 1.6 and T/N < 1.6 in each tumor type. Median observation period was 434 days after met-PET scanning. Results: The number of patient who underwent recurrence was 10 in DA, 7 in AA, and 11 in GB. All patients showing T/N > 1.6 underwent tumor recurrence. PFS was significantly longer in patients with T/N < 1.6 than T/N > 1.6 in DA and AA (p < 0.01 in both types), but was no significant difference between 2 groups in GB (p = 0.06). Sixteen of 17 patients (94%) in DA and AA showed recurrence from residual tumor, whereas 4 of 11 patients (36%) in GB showed recurrent tumor at remote regions which were different from residual tumor. Conclusions: The present study suggested that met-PET is beneficial to decide to discontinue adjuvant chemotherapy with TMZ in patients with residual tumors of DA and AA, but not useful for patients with GB. Reasons for unsuccessful results in GB might have been small sample size, failure of establishing the cut off value in T/N, recurrences at remote regions where not be assessed by met-PET.